FAKTOR YANG MEMPENGARUHI MINAT MILENIAL DALAM MENGGUNAKAN JASA PEGADAIAN SYARIAH - Desiana, Rina; Ihsan, Faryal Musnadi (Jihbiz: Global Journal of Islamic Banking and Finance, 2023)
The presence of sharia pawnshops can also have a positive impact because the main purpose of pawnshops is to help people who are in need of funds so they are free from bondage to bondage practices. The purpose of this research is to find out the Factors Influencing Millennial Interest in Using Sharia Pawnshop Services. This research method uses a quantitative method with data collection techniques by distributing questionnaires to 100 respondents, namely the people of Southwest Aceh Regency who belong to the millennial generation and also sharia pawnshop customers. The partial test results show that the location variable (X1) has no significant effect on millennial interest in using sharia pawnshop services, while the Promotion Variable (X2) and Service Quality (X3) has a significant effect on millennial interest in using sharia pawnshop services. Furthermore, the results of the simultaneous test show that the variables of location, promotion, and service quality jointly affect millennial interest in using sharia pawnshop services